2017
DOI: 10.1002/jum.14472
|View full text |Cite
|
Sign up to set email alerts
|

Size and Ultrasound Features Affecting Results of Ultrasound‐Guided Fine‐Needle Aspiration of Thyroid Nodules

Abstract: Tiny nodules (≤5 mm) with obscure borders tended to yield false-positive FNA results. Large nodules (>20 mm) with several US features tended to yield false-negative FNA results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…They found that diagnostic accuracy was best in nodules sized 5 to 10 mm in diameter, and the false negative rate increased with increasing nodule size (> 20 mm), and false positive highest in the smallest nodules (< 5 mm). However, the majority of these nodules were micronodules (mean size 10.8 +/-7.6 mm) [13]. Without information on ultrasound characteristics in this study, we were unable to determine whether size or cystic nodules influenced the ND rate.…”
Section: Non-diagnostic Rates By Procedural Volume and Rosementioning
confidence: 78%
“…They found that diagnostic accuracy was best in nodules sized 5 to 10 mm in diameter, and the false negative rate increased with increasing nodule size (> 20 mm), and false positive highest in the smallest nodules (< 5 mm). However, the majority of these nodules were micronodules (mean size 10.8 +/-7.6 mm) [13]. Without information on ultrasound characteristics in this study, we were unable to determine whether size or cystic nodules influenced the ND rate.…”
Section: Non-diagnostic Rates By Procedural Volume and Rosementioning
confidence: 78%
“…Ultrasound and elastography both showed higher sensitivity for nodules larger than 10 mm and higher specificity for nodules smaller than 10 mm . Small nodules (≤5 mm) may also cause false‐positive FNAB results, whereas large nodules (>20 mm) tend to produce false‐negative FNAB results . We examined nodules that were larger than 1.5 cm and smaller than 1.5 cm, and we could not find a relationship between nodule size and malignancy.…”
Section: Discussionmentioning
confidence: 93%
“…32 Small nodules (≤5 mm) may also cause false-positive FNAB results, whereas large nodules (>20 mm) tend to produce false-negative FNAB results. 33 We examined nodules that were larger than 1.5 cm and smaller than 1.5 cm, and we could not find a relationship between nodule size and malignancy. We avoided nodules larger than 40 mm, as well as pure cystic and rough calcified nodules because these nodules were difficult to evaluate accurately for the SR, as described in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Shows the overview of FNA findings in both groups with its final surgical pathology findings (P-FNA: palpation-guided FNA; US-FNA: ultrasound-guided FNA). the diagnostic accuracy of US-guided FNA based on size and US findings [26]. The authors suggested that patients with smaller nodule size (≤5 mm) are more likely to have falsepositive findings; while the chances of false-negative FNA findings is more with larger thyroid nodules (>20 mm) and remarkable US features.…”
Section: Discussionmentioning
confidence: 99%